The Principle of Determining the Country’s Baseline Point That Shifts as An Impact of Climate Change - Wita Setyaningrum (JUSTITIA JURNAL HUKUM, 2025)
Based on natural conditions, the State Baseline measurement method for coastal areas is usually with a low water level mark, which differs between coastline areas in each country. This means that it is not possible to have permanent borders for a maritime country that can be used. Any movement or shift of the State Baseline is not regulated by the provisions of UNCLOS 1982. This condition is expected to give rise to international disputes, including with other maritime zones. With the phenomenon of climate change becoming more pronounced, there are gradual changes in coastlines, and there are no specific provisions regarding this in UNCLOS 1982. As such, the provisions contained in UNCLOS 1982 cannot respond effectively to the phenomena of shifts that occur in coastline, which will also influence the determination of sea baselines to determine the start of a country's territorial sea. So in conditions like this, the existence of UNCLOS cannot be said to be an international instrument capable of adapting to conditions occurring on earth. With this climate change phenomenon which has an impact on shifting the State Baseline, of course it gives rise to various kinds of new problems and challenges in the existing international legal structure regarding maritime law. Namely how the baselines are set in UNCLOS 1982 where the phenomenon of climate change and the consequences of sea level rise can cause changes in the determination of the baseline points that have been measured in terms of the Principle of State Sovereignty. This research to analyze international legal arrangements and discover new arguments in determining the principle of state sovereignty as a basis for shifting baselines due to climate change. This type of research is normative juridical research. The data collection method used is literature study. The tool used in this research is secondary data in the form of documents consisting of primary legal material, secondary legal material and non-legal material. The data was analyzed qualitatively and then presented descriptively.